2010
DOI: 10.1038/nature08882
|View full text |Cite
|
Sign up to set email alerts
|

Zscan4 regulates telomere elongation and genomic stability in ES cells

Abstract: Exceptional genomic stability is one of the hallmarks of mouse embryonic stem (ES) cells. However, the genes contributing to this stability remain obscure. We previously identified Zscan4 as a specific marker for 2-cell embryo and ES cells. Here we show that Zscan4 is involved in telomere maintenance and long-term-genomic stability in ES cells. Only 5% of ES cells express Zscan4 at a given time, but nearly all ES cells activate Zscan4 at least once within nine passages. The transient Zscan4-positive state is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
571
4
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(603 citation statements)
references
References 48 publications
25
571
4
3
Order By: Relevance
“…The fact that the EMT-inducing transcription factor SNAIL uses an histone-specific demethylation to cause one of its major effects, the downregulation of E cadherin, implies relatively long time-scale effects . The maintenance of telomeres in ESCs required telomerase expression only once in nine passages (Zalzman et al, 2010). We have seen that DTP phenotypes switch back to normal after 30 generations.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The fact that the EMT-inducing transcription factor SNAIL uses an histone-specific demethylation to cause one of its major effects, the downregulation of E cadherin, implies relatively long time-scale effects . The maintenance of telomeres in ESCs required telomerase expression only once in nine passages (Zalzman et al, 2010). We have seen that DTP phenotypes switch back to normal after 30 generations.…”
Section: Discussionmentioning
confidence: 83%
“…The permanence of CSC-TPC properties is questionable. ESCs (embryonic stem cells (ESS)) elongate their telomers once in nine passages, indicating, in this case, a sequential dynamic process (Zalzman et al, 2010). Such a dynamic view applies even to cell lines in culture.…”
Section: Csc-tpc Quiescent or Proliferative?mentioning
confidence: 99%
“…We next performed immunofluorescence analyses and found that although the percentage of γ-H2AX-positive cells among cells undergoing reprogramming did not differ between the two groups (37.00% ± 2.96% in OSKM vs 34.19% ± 1.34% in OSKMZ, P = 0.389) ( Figure 2B), γ-H2AX-positive foci were more abundant in OSKM-infected cells than in OSKMZ-infected cells ( Figure 2B). Furthermore, colocalization of γ-H2AX and Trf1, indicative of telomere-induced DNA damage foci [28][29][30], was significantly reduced in OSKMZ-infected cells as compared to OSKM-infected cells ( Figure 2C). Because γ-H2AX is a marker for DSBs [31], we tested general sister chromatid exchange (SCE) [32,33] in reprogramming cells.…”
Section: Zscan4 Improves Genomic Stability During Reprogrammingmentioning
confidence: 87%
“…Because Zscan4 expression is associated with the maintenance of genomic stability in ES cells, likely by rapid telomere elongation [28], we speculated that Zscan4 induction might contribute to telomere extension during reprogramming. We examined relative telomere length by quantitative telomere FISH (Q-FISH) [38] in OSKM-and OSKMZ-infected MEFs on days 3 and 6 post-infection.…”
Section: Zscan4 Promotes Telomere Elongation During Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation